Educação Popular em Saúde e política de drogas: desmistificando a proibição da maconha e combatendo a opressão estatal - Gonçalves, Vinícius Viana (2026)
This Course Completion Work, submitted to the National Specialization in Popular Health Education at the Fiocruz Brasília School of Government, analyzes the intersection between Popular Health Education, grounded in Paulo Freire's pedagogy, and drug policies in Brazil, with emphasis on marijuana prohibition. Prohibitionism, exemplified by Law 11.343/2006, reinforces racial and class inequalities, fuels mass incarceration—with about 25-30% of the prison population linked to drug crimes, predominantly young Black and poor individuals from peripheries—and perpetuates state oppression through penal selectivity and institutional violence. This criminalizing approach ignores scientific evidence on Cannabis's medicinal uses, such as in Alzheimer's treatment and other neurological conditions, as well as economic potentials for family farming, job generation, and reduction of violence tied to the illicit market. The qualitative methodology employs critical analysis of documentary, legal, media, and institutional sources, including Freire's works, Fiocruz reports, prison system data, and experiences of Cannabis associations promoting self-management and democratic access to cannabidiol. "Tempo-Comunidade" experiences in Rio Grande/RS reveal community potentials, such as Afro-Brazilian ancestral knowledge, cultural collectives, and conversation circles, which resist stigma and build alternative narratives of care and dignity. Popular Health Education emerges as an emancipatory strategy to demystify prohibitionist myths, foster horizontal dialogue, collective awareness, and pressure for regulated legalization, aligned with the SUS and harm reduction. The results highlight benefits of legalization, such as market democratization, strengthening of regional economies, and integration of popular knowledge with science, combating the failed "war on drugs." It concludes that Popular Health Education is essential for transforming drug policies into humanized practices cente